(Hi)Stories of desire : sexualities and culture in modern India - Kumaramkandath, Rajeev (ed.); Srivastava, Sanjay (ed.); Indian Institute of Advanced Study (New Delhi Cambridge University Press, 2020)
(Hi)Stories of Desire situates questions of sexuality in the larger domain where they are conditioned by and, in turn, also condition historically and culturally produced landscapes of being, doing and desiring. The book draws upon multi-disciplinary frameworks of analysis - including history, anthropology, literary studies, queer studies and psychoanalysis - to provide a pan-Indian account of the making of sexual cultures. Based on original research, the chapters foreground sexuality as a significant site for the making of regional, national and personal modernities. The volume addresses the modern paradox where sexuality is assigned a central significance in human life and yet its study tends to remain unconnected from the political, religious, social and economic contexts that produce human subjectivity. It will be of interest to a wide range of readership, opening up the topic to complex yet accessible ways of understanding the culture of sexualities and the sexuality of culture.
"The origins of this book lie in a seminar at the Indian Institute of Advanced Studies (IIAS), Shimla, in September 2014"--Acknowledgements.
Includes bibliographical references and index.
Keywords: Sexual minorities; Sex customs; Man-woman relationships